A Systematic Literature Review: Implementation of Local Wisdom-Based Educational Media in Science Learning to Strengthen Students' Characters - Joni Rokhmat; Susilawati; Muh Makhrus; AA Sukarso; Huraiza Mahmudah; Gina Harnum Fatina (International Journal of Contextual Science Education, 2024)
This study aims to examine the implementation of educational games based on local wisdom in science learning to strengthen students' character. The method used​ is to review the literature. Method review literature identifies, examines, evaluates, and interprets all existing research​ on an interesting phenomenon, with​ questions that study certain relevant ones. The number of articles analyzed in this research was nine articles. Implementation of educational media in learning in the form of teaching models and modules, games and traditional food. Based on the results of the analysis, several forms of local wisdom were obtained, which were integrated into educational media, such as the rumpe ritual, traditional Minangkabau food: Ampiang Dadiah, the traditional ball boy game, local wisdom Trikaya Prisudha, local wisdom of the coastal area Puger, traditional games of tug of war, making Madurese shrimp paste, and local wisdom of Manongkah shellfish. The character values that can be instilled by implementing educational media based on local wisdom in learning are twenty-four character values. The character values most often instilled in implementing.